Who wrote II Thessalonians? - Bailey, John A. (New Testament studies, 1979)
Since World War II a considerable number of New Testament scholars (many of them German) have come to the conclusion that Paul did not write II Thessalonians. Among these the names of Rudolf Bultmann, Günther Bornkamm, Willi Marxsen, and Helmut Koester come to mind. What is curious is that to date no single commentary has appeared in any major European language which interprets II Thessalonians as pseudonymous. C. Masson in the introduction to his commentary decides against Pauline authorship, but in the commentary itself interprets as though Paul were the author – an anomaly perhaps related to his view of pseudonymity. The forth-coming commentaries of Marxsen and Koester will therefore provide scholars with the first examples of exegesis of the letter as non-Pauline. Since the issue of authorship is evidently by no means settled, the present article examines the evidence for both positions and concludes with a discussion of pseudonymity in the ancient world.